Powering biomedical devices - Romero, Edwar (Academic Press, 2013)
From exoskeletons to neural implants, biomedical devices are no less than life-changing. Compact and constant power sources are necessary to keep these devices running efficiently. Edwar Romero's Powering Biomedical Devices reviews the background, current technologies, and possible future developments of these power sources, examining not only the types of biomedical power sources available (macro, mini, MEMS, and nano) but also what (powered prosthesis, insulin pumps, muscular and neural stimulators, etc.) and how (using batteries, telemetry, etc.) they power. By briefly examining these key aspects, this book gives its readers a valuable overview of biomedical devices' power sources.